Identification of Novel Proteins from Black Cumin Seed Meals Based on 2D Gel Electrophoresis and MALDI-TOF/TOF-MS Analysis - (:unkn) unknown (SPRINGER, 2019)
The amount of cold press oil manufacture is globally rising, which in turn leads to the accumulation of deoiled plant seeds at significant quantities and consequent manufacture of plant protein products. In this study, we made an attempt to analyze the protein profile of black cumin seed protein concentrates prepared by the alkali extraction-acid precipitation technique (AE-IP). The analytical strategy relied on gel-based proteome mapping which included two-dimensional gel electrophoresis followed by matrix-assisted laser desorption/ionization-time of flight (MALDI-TOF/TOF). 14 different protein bands were identified, and in gel-trypsinolysis was carried out for the corresponding gel spots. Using the MASCOT database, current findings on 10 proteins were compared with the existing data. The highest similarity was 46 which was obtained between the highest pI black cumin protein observed here and the cyclin dependent kinase inhibitor of Arabidopsis thaliana. The molecular mass of the intact protein was determined by linear MALDI-TOF/TOF-MS as 23,711.2186 Da. The peptide constructs of this protein have been further studied in order to identify potential biological activity. Matching sequences generated bioactive peptides in silico such as IR, AL, and SL dipeptides during sequential enzymatic digestion with pepsin and trypsin. Since the majority of bioactivity investigations on black cumin seeds have been related to black cumin oil and its oil soluble components, the structure and bioactivities of black cumin proteins deserve further research.
Keywords: Black cumin; Protein concentrates; Proteomic analysis; 2D-gel electrophoresis; In gel trypsinolysis; MALDI-TOF; TOF; NIGELLA-SATIVA